N7-Tosyltheophylline (TsTh): A Highly Efficient Reagent for the One-Pot Synthesis of N7-Alkyltheophyllines from Alcohols - Soltani Rad, Mohammad Navid; Behrouz, Somayeh; Najafi, Hosnieh (Synthesis, 2014)
A convenient and highly efficient one-pot N-alkylation of theophylline from alcohols via N7-tosyltheophylline (TsTh) is described. In this protocol, the treatment of primary and/or secondary alcohols with a mixture of TsTh and 1,8-diazabicyclo[5.4.0]undec-7-ene in refluxing acetonitrile affords the corresponding N7-alkyltheophylline in good to excellent yields; the reaction was optimized for solvent and base. This methodology is highly efficient for various structurally diverse primary and secondary alcohols. A plausible mechanism for the one-pot N-alkylation of theophylline with alcohols via TsTh has been suggested.
Keywords: N-alkylation; alcohol; theophylline; TsTh; DBU